2007
DOI: 10.1080/13632460701457116
|View full text |Cite
|
Sign up to set email alerts
|

Site Classification Using Horizontal-to-vertical Response Spectral Ratios and its Impact when Deriving Empirical Ground-motion Prediction Equations

Abstract: We classify sites based on their predominant period computed using average horizontal-tovertical (H/V) response spectral ratios and examine the impact of this classification scheme on empirical ground-motion models. One advantage of this classification is that deep geological profiles and high shear-wave velocities are mapped to the resonance frequency of the site. We apply this classification scheme to the database of Fukushima et al. (2003), for which stations were originally classified as simply rock or soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 12 publications
5
51
1
Order By: Relevance
“…They introduced an empirical site classification method based on the mean horizontal to vertical ratio of the acceleration response spectra (HVRSR), calculated assuming a 5% damping, across all periods for strong-motion stations in Japan. Fukushima et al (2007) classified sites based on their predominant period computed using average horizontal-to-vertical response spectra ratios and examined the impact of this classification scheme on empirical ground-motion prediction equations. The classification scheme was applied to the database by Fukushima et al (2003), and the aleatoric variability of these equations (measured by their standard deviations) was slightly lower than those derived using the simple soil or rock subdivision.…”
Section: Introductionmentioning
confidence: 99%
“…They introduced an empirical site classification method based on the mean horizontal to vertical ratio of the acceleration response spectra (HVRSR), calculated assuming a 5% damping, across all periods for strong-motion stations in Japan. Fukushima et al (2007) classified sites based on their predominant period computed using average horizontal-to-vertical response spectra ratios and examined the impact of this classification scheme on empirical ground-motion prediction equations. The classification scheme was applied to the database by Fukushima et al (2003), and the aleatoric variability of these equations (measured by their standard deviations) was slightly lower than those derived using the simple soil or rock subdivision.…”
Section: Introductionmentioning
confidence: 99%
“…Following Zhao et al [2], Fukushima et al [21] and Di Alessandro et al [1], we first evaluated the H/V ratios of the 5%-damped response spectra of the recorded earthquakes. The use of the response spectra instead of classical Fourier spectra is justified because it is largely used by engineers and has the advantage that the damping automatically removes most of the spikes in the spectra obtaining a smoothed shape [26].…”
Section: Methodsmentioning
confidence: 99%
“…When classifying site classes of Taiwan free-field strong motion stations, Lee et al (2001) concluded that this method is very helpful for evaluating class of a site where the geological and geotechnical information is lacking, and its classification results are reliable by comparing with the results of Kuo (1992Kuo ( , 1993Kuo ( , 1994. Fukushima et al (2007) discussed that although the HVSR method has a shortcoming for the site with a broadband response, in most cases it is useful for site classification even when information on the soil profile is lacking. Furthermore, the HVSR method is improved by designing a new index for probabilistic distribution of spectral shape (Ghasemi et al, 2009), or using neural network technique (self-organizing map, SOM) (Garniel et al, 2009), which makes the method more reasonable.…”
Section: Hvsr Classificationmentioning
confidence: 98%